Melting of PCM inside a novel encapsulation design for thermal energy storage system. (September 2021) - Mohaghegh, M.R.; Alomair, Y.; Alomair, M.; Tasnim, S.H.; Mahmud, S.; Abdullah, H.
Highlights: The novel pear-shaped geometry is proposed for TES systems with high thermal performance. The three different heat transfer regimes are observed during the melting process. Unconstrained melting shows to be almost twice faster than constrained melting. The effect of the capsule shape is prominent on the melting process as the uniform melting front is observed. The numerical melting patterns and the melt fractions show an excellent agreement with experimental visualizations. Abstract: Phase Change Materials (PCMs) encapsulated inside different shape and size enclosures have been playing an important role in designing thermal energy storage (TES) systems for a wide range of applications. In the present work, transient heat transfer and the melting process of n-octadecane PCM encapsulated in a novel Pear-Shaped Thermal Energy Storage (PS-TES) system with and without constraint are numerically investigated and verified with experimental visualizations. An adiabatic cylindrical rod, placed at the axis of symmetry of the pear-shaped enclosure, is used to create the constraint. A mathematical model is developed and numerically solved to study energy transport processes inside the proposed PS-TES systems. The heat transfer characteristics such as melt fraction, Nusselt number, and energy stored in the system and their temporal variation during the melting process are determined. The melting process is visualized numerically to track the solid-liquid interface during the melting process as well. Comparison of results from the unconstrained and constrained cases reveals that the existence of the adiabatic constraint inside the system decreases the melting rate, as the total time required to complete the melting process in the constrained melting (~178 min) is almost twice that of unconstrained melting (~97 min). The effect of the Rayleigh number on the melt fraction, Nusselt number, and the stored energy is studied and discussed as well. Furthermore, a comparison between the melt fraction results for pear-shaped system and a convectional cylindrical container with the same height and same volume shows that the complete melting time for the PS-TES system (~97 min) is less compared to the one for the cylindrical case (~108 min). A comprehensive experimental setup is also developed using a constant temperature bath and thermal regulator to visualize melting images and track the melting front during the phase change process. Numerical images of heat transfer field and solid-liquid interface, as well as the temporal variation of melt fraction in both test cases, are compared with experimental visualizations, and an excellent agreement is reported.